Neue Erkenntnisse über den Fluoridgehalt im Krill (Euphausia superba Dana) - Christians, O.; Leinemann, M.; Manthey, Monika (1981)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010